Techno-environmental optimal sizing and dynamic behavior of a hybrid system feeding a large-scale SWRO desalination system: The case of Djerba Island, Tunisia - Mohamed Hamdi; Oumayma Gtari; Majdi Hazami (Energy Exploration & Exploitation)
The environment, energy, and water are the three essential pillars of sustainable development. In light of the freshwater scarcity faced by numerous countries, desalination emerges as a practical solution. As a result, countries are increasingly establishing desalination facilities along their coastlines. However, these initiatives are energy-intensive, and their chosen locations may not be optimal for harnessing renewable energy resources. With a daily output capacity of 50,000 m 3 , the recently operational seawater desalination plant in Djerba, Tunisia, accounts for 13.6% of the region's total electrical energy consumption. In this study, we have considered both the specific and the overall desalination consumption to find the optimal architecture and assess the reliability of the hybrid energy generator supplying the unit. The economic optimization has been performed using hybrid optimization of multiple energy resources, and the dynamic study of the complete system has been achieved using the transient system simulation tool environment. On- and off-grid scenarios using various hybrid power system combinations with and without batteries were proposed and examined. Results showed that the optimum case consists of on-grid 60.513 MWp solar panels and 13.64 MW wind turbines with battery storage. The water produced by the most cost-effective strategy with regard to environmental protection for a 25-year project life cycle costs 0.414 $/m 3 against 0.585 $/m 3 for current consumption. This significant reduction in water production costs makes desalination more affordable and accessible. The dynamic behavior of the optimal architecture is designed by considering the real meteorological data of Djerba Island. In terms of productivity, the maximum photovoltaic and wind energy production reached 11.31 GWh in July and 0.51 GWh in April, respectively. The findings demonstrate the technical and economic feasibility of powering large-scale desalination plants with hybrid renewable energy systems, reducing their environmental impact and energy costs. The optimal system proposed in this study can serve as a model for future desalination projects in Tunisia and other water-scarce regions.